A Temporary Immersion System to Improve Cannabis sativa Micropropagation - Rico, Saleta; Garrido, José; Sánchez, Conchi; Ferreiro-Vera, Carlos; Codesido, Verónica; Vidal, Nieves (Frontiers in Plant Science, 2022)
The aim of this study was to propagate axillary shoots of Cannabis sativa L. using liquid medium in temporary immersion bioreactors. The effect of immersion frequency (3 or 6 immersions per day), explant type (apical or basal sections), explant number (8, 10, and 16 explants), mineral medium (Murashige and Skoog half-strength nitrates, β-A and β-H, all supplemented with 2-μM metatopoline), sucrose supplementation (2, 0.5, and 0% sucrose), culture duration (4 and 6 weeks), and bioreactor type (RITA® and Plantform™) were investigated. As a result, we propose a protocol for the proliferation of cannabis apical segments in RITA® or Plantform™ bioreactors. The explants (8 per RITA® and 24 per Plantform™) are immersed for 1 min, 3 times per day in β-A medium supplemented with 2-μM metatopoline and 0.5% of sucrose and subcultured every 4 weeks. This is the first study using temporary immersion systems in C. sativa production, and our results provide new opportunities for the mass propagation of this species.